If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5f + 4 + -3f = 20 Reorder the terms: 4 + 5f + -3f = 20 Combine like terms: 5f + -3f = 2f 4 + 2f = 20 Solving 4 + 2f = 20 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 2f = 20 + -4 Combine like terms: 4 + -4 = 0 0 + 2f = 20 + -4 2f = 20 + -4 Combine like terms: 20 + -4 = 16 2f = 16 Divide each side by '2'. f = 8 Simplifying f = 8
| 4(x-4+4)-10x=30 | | (14x+10)+(16x-4)=180 | | 24u^4w^5x^7-20u^6w^9= | | 20=1 | | 4x-4+4-10x=30 | | 30u^2w^5+5u^8w^4y^9= | | 0=.088x^2+2.5x | | 40-8x=-56-12x | | -3(3+5x)=-144 | | 2(x+3)-8x=42 | | nx-r=pforx | | 3(x+3)+2x=29 | | -3(3+5x)=-112 | | 18uv^2w^3+30u^6v^5= | | -6(5+x)=24 | | 3y-6+y+40=8y+40-6y | | No-r=p | | 4(5-x)(x+6)=0 | | 0P=30 | | 6x-(5-4x)=5 | | (x^2-6x+5)(7x-4)= | | 7x+8=108-3x | | 45-7x=-31-11x | | 3(1-x)=-3(x+2) | | (7y^2+5y-6)(7y^2+4y+1)= | | 8+6x=-x-55 | | 2(3+5x)+2(5x+3)=92 | | 3(-2x-3)-2=10-3x | | 6x-3(5x+4)=-3(3x+4)+6 | | 6+6x=-7x+123 | | 3f-5d=10 | | -1-3x+7x=-9 |